A Systematic Review of the Impact of Viral Respiratory Epidemics on Mental Health: An Implication on the Coronavirus Disease 2019 Pandemic - Luo, Yang; Chua, Cher Rui; Xiong, Zhonghui; Ho, Roger C.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2020)
Background: 21st century viral respiratory epidemics have taught us valuable lessons. Our systematic review examined the impact of these epidemics, including Coronavirus Disease 2019 (COVID-19), on mental health amongst different population groups, drawing on their insights for recommendations for the current COVID-19 pandemic. Methods: Searches were performed on PubMed, Embase, PsycINFO, Web of Science, Scopus, CINAHL, and Cochrane on April 4th, 2020. Studies that had undefined mental health outcomes or did not use a validated scale for measure were excluded. Quality assessment was carried out via the Newcastle-Ottawa Scale (NOS). Results: We included 95 studies, most of which were conducted in Hong Kong (31.6%) and China (21.4%). 30 (30.9%) studies are on the general public, 41 (42.2%) on healthcare workers, and 26 (26.6%) on patients and quarantined individuals. 36 (37.1%) of the studies are of high-quality, 48 (49.5%) are of moderate-quality, and 13 (13.4%) are of low-quality. The most significant mental health outcomes reported include anxiety, depression and post-traumatic stress disorder symptoms. Subgroups identified to have higher risk of psychiatric symptoms among the general public include: females, the elderly, individuals with chronic illness, migrant workers, and students. Long-term mental health impact was reported in some healthcare workers and epidemic patients, even up to 3 years in the former. Interestingly, when compared to non-quarantined groups, quarantine was not significantly associated with worse mental health outcomes. Conclusion: Important implications for the COVID-19 pandemic were highlighted. Respiratory epidemics pose significant psychological morbidity onto many population groups. Psychological support for vulnerable groups, including healthcare workers and patients, should be implemented to prevent them from spiralling into clinical psychiatric conditions.